Zonificación agroclimática para el manejo de SchizolobiumPparahybum (Vell.) Blake (pachaco) en la provincia los Ríos - Rivera Manrique, Gary Daniel (2020)
Among the variables of greatest interest for the growth and development of agricultural and forest species are air temperature and precipitation, and although an agroclimatic zoning also considers other variables, such as the changes found in air temperature and precipitation, which It manifests itself in the growth and development of forest plantations. The interannual climatic variability, the attack of plagues and the droughts constitute other variables that have an impact on the agricultural and forestry production The objective of the investigation was to determine the favorable periods and the ideal areas depending on the agroclimatic conditions for the Pachaco plantations. A climatic database of the INAHMI and the ClimWat of the FAO of Los Ríos province was used. The AgroclimMap software that performs agroclimatic analyzes and presents the results in the form of maps was applied, highlighting the favorable level of the province for the growth and development of the pachaco. It was found that favorable conditions for the province, in general, are in the moderately favorable - favorable range, with 11% and 73.3% of the area, respectively. Only Non-Favorable conditions are presented, with 15.3% of the area, at the Patricia Pilar, Valencia, Los Angeles, Valencia Norte and El Copal reference stations. The 25% percentile for the sum of annual rainfall indicated that the probability of drought for the pachaco is very low, since it includes the Favorable category and in the upper limit the Moderately Favorable category. On the other hand, in the 75% percentile it was found that there is a risk of flooding for the stations to the North, with excesses ascending to 687 mm. It is recommended that similar studies be carried out in other provinces and that the results be related to the net primary productivity that allow estimates of yields. Keyword: Air temperature, rainfall, silviculture, climatic requirements